Disordered Substrates of the 20S Proteasome Link Degradation with Phase Separation. Issue 21 (20th August 2018) - Guharoy, Mainak; Lazar, Tamas; Tompa, Peter
Abstract: The 20S proteasome is known to degrade intrinsically disordered proteins (IDPs) via an ubiquitin‐independent, disorder‐driven mechanism. Unless protected within protein complexes or macromolecular assemblies, certain IDPs can undergo degradation mediated directly by the 20S core particle. In this issue of Proteomics, Myers et al. utilize a proteomics approach to identify ∼500 IDP substrates of the 20S proteasome. Bioinformatics analyses of these substrates demonstrate a large fraction of highly disordered RNA‐binding proteins, enriched in low‐complexity, prion‐like domains. A number of these proteins are also known to form phase‐separated membraneless organelles in amyotrophic lateral sclerosis (ALS) and other protein neuropathies. The Myers et al. study highlights potentially interesting connections between IDP degradation and the regulatory dynamics of phase‐separated intracellular assemblies. Their work should stimulate further research into the mechanistic details of how the 20S proteasome controls cellular abundances of RNA‐binding proteins and thereby regulates RNA‐related biological functions within both physiological and pathological phase‐separated assemblies.